Assessing the Capability of ChatGPT, Google Bard, and Microsoft Bing in Solving Radiology Case Vignettes - Pradosh Kumar Sarangi; Ravi Kant Narayan; Sudipta Mohakud; Aditi Vats; Debabrata Sahani; Himel Mondal (Indian Journal of Radiology and Imaging, 2024)
Background The field of radiology relies on accurate interpretation of medical images for effective diagnosis and patient care. Recent advancements in artificial intelligence (AI) and natural language processing have sparked interest in exploring the potential of AI models in assisting radiologists. However, limited research has been conducted to assess the performance of AI models in radiology case interpretation, particularly in comparison to human experts.